Direct costs of acute respiratory infections in a pediatric long‐term care facility. Issue 1 (January 2016) - Murray, Meghan T.; Heitkemper, Elizabeth; Jackson, Olivia; Neu, Natalie; Stone, Patricia; Cohen, Bevin; Saiman, Lisa; Hutcheon, Gordon; Larson, Elaine L.
Abstract : Acute respiratory tract infections (ARI) are a major burden in pediatric long‐term care. We analyzed the financial impact of ARI in 2012–2013. Costs associated with ARI during the respiratory viral season were ten times greater than during the non‐respiratory viral season, $31 224 and $3242 per 1000 patient‐days, respectively ( P  < 0·001). ARI are burdensome for pediatric long‐term care facilities not only because of the associated morbidity and mortality, but also due to the great financial costs of prevention.